The effect of family involvement in diabetes self-management education on glycemic control in patients with type 2 diabetes mellitus: a systematic review and meta-analysis - Azmiardi, Akhmad; Murti, Bhisma; Febrinasari, Ratih Puspita; Tamtomo, Didik Gunawan (Journal of Public Health and Development, 2021)
Diabetes self-management education (DSME) is an essential part of diabetes care. It is possible to deliver DSME in many forms and components. In this case, family support is known to be a critical component of social support in self-care and glycemic control. This study aimed to systematically review the effectiveness of family involvement in diabetes self-management education for glycemic control in patients with type 2 diabetes mellitus. The researchers searched PubMed, SpringerLink, Science Direct, Google Scholar, and EBSCO for English and Indonesian articles published between 2000 and 2020 describing randomized controlled trials involving family components. The primary outcome of this review was HbA1c changes. The pooled standard mean differences (SMD) or effect size between intervention and control groups with 95% confidence interval (CI) were calculated using a random-effects model. Meanwhile, heterogeneity of HbA1c findings was assessed with Cochran’s Q and I2. Seventeen randomized controlled trials with a total of 2644 participants were obtained from a comprehensive search procedure. The intervention was effective in reducing HbA1c (SMD= -0.31 95%CI= -0.46 to -0.16;) than the control group, and it was statistically significant (p<.001). Due to heterogeneity (I2 = 71%), a meta-analysis of the random-effects model was employed. Intervention program with baseline HbA1c < 9% (SMD= -0.55; 95%CI= -1.05 to -0.05; p=.030), duration of intervention ≥ 6 month (SMD= -0.26; 95%CI= -0.37 to -0.15; p<.001), intervention delivery mode of combination type (SMD= -0.73; 95%CI= -1.42 to -0.03; p=.040), contact hour ≥10 (SMD= -0.37; 95%CI= -0.59 to -0.14; p=.001), and frequency of contact (SMD= -0.75; 95%CI= -1.39 to -0.12; p=.020) were effective to reduce HbA1c level. According to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method, the quality of evidence was classified as moderate. Family involvement in the DSME program was effective in improving glycemic control in patients with type 2 diabetes. Further research on baseline HbA1c, delivery mode, contact hours, and intervention frequency may provide useful information to determine the most effective treatment.